Explore on the Mechanism of miRNA-146a/TAB1 in the Regulation of Cellular Apoptosis and Inflammation in Ulcerative Colitis Based on NF-κB Pathway - Xia, Xiaoying; Yang, Qian; Han, Xue; Du, Yulin; Guo, Shujun; Hua, Mengqing; Fang, Fang; Ma, Zhigang; Ma, Hua; Yuan, Hui; Tian, Wenjing; Ding, Zebang; et al. (Current Molecular Medicine, 2025)
Objective Ulcerative colitis (UC) is a chronic non-specific inflammatory disease of the rectum and colon with unknown etiology. A growing number of evidence suggest that the pathogenesis of UC is related to excessive apoptosis and production of inflammatory cytokines. However, the functions and molecular mechanisms associated with UC remain unclear. Materials and Methods The in vivo and in vitro models of UC were established in this study. MiRNA or gene expression was measured by qRT-PCR assay. ELISA, CCK-8, TUNEL, and flow cytometry assays were applied for analyzing cellular functions. The interactions between miR-146a and TAB1 were verified by luciferase reporter and miRNA pull-down assays. Results MiR-146a was obviously increased in UC patients, DSS-induced colitis mice, and TNF-ɑ-induced YAMC cells, when compared to the corresponding controls. MiR-146a knockdown inhibited the inflammatory response and apoptosis in DSS-induced colitis mice and TNF-ɑ-induced YAMC cells. Mechanistically, we found that TAB1 was the target of miR-146a and miR-146a knockdown suppressed the activation of NF-κB pathway in UC. More importantly, TAB1 could overturn the inhibitory effect of antagomiR-146a on cell apoptosis and inflammation in UC. Conclusion MiR-146a knockdown inhibited cell apoptosis and inflammation via targeting TAB1 and suppressing NF-κB pathway, suggesting that miR-146a may be a new therapeutic target for UC treatment.
Keywords: inflammation